Semi-analytical and semi-numerical method for the single soil layer consolidation problem. Issue 3 (2nd May 2017) - Cheng, Tao; Yan, Keqin; Zheng, Jun-Jie; Luo, Xian-Feng; Zhang, Ding-Bang; Xu, Wan-Hui; Hu, Ren-Jie; Zhang, Yi
Abstract : Purpose: This paper aims to present a simplified solution method for the elasto-plastic consolidation problem under different stress paths. Design/methodology/approach: First, a double-yield-surface model is introduced as the constitutive model framework, and a partial derivative coefficient sequence is obtained by using numerical approximation using Gauss nuclear function to construct a discretization constitutive model which can reflect the influence of different stress paths. Then, the model is introduced to Biot's consolidation theory. Volumetric strain of each step as the right-hand term, the continuity equation is simplified as a Poisson equation and the fundamental solution is derived by the variable separation method. Based on it, a semi-analytical and semi-numerical method is presented and implemented in a finite element program. Findings: The method is a simplified solution that is more convenient than traditional coupling stiffness matrix method. Moreover, the consolidation of the semi-infinite foundation model is analyzed. It is shown that the numerical method is sufficiently stable and can reflect the influence of stress path, loading distribution width and some other factors on the deformation of soil skeleton and pore water pressure. Originality/value: Original features of this research include semi-numerical semi-analytical consolidation method; pore water pressure and settlements of different stress paths are different; maximum surface uplift at 3.5a; and stress path is the main influence factor for settlement when loading width a > 10 m.